Exploring the experiences of mothers of children with developmental disabilities - Bond, Courtney (2014)
This qualitative study explores the experiences of mothers who have children with developmental disabilities. I sought to understand both the positive aspects of mothering a child with a disability, as well as understand the potential negative aspects of mothering a child with a developmental disability. I also explored how the mothers reflected on this experience of mothering a child with a disability. Furthermore, I sought information on what services and/or supports these mothers found helpful, and why. Six mothers were interviewed for this study. From these interviews, six themes were identified: 1. positive experiences and emotions; 2. mothering a child with a developmental disability as difficult, stressful, and overwhelming work; 3). mothers’ fears for their children; 4). mothers’ sense of loss; 5). mothers’ relationships with their non-disabled children; and 6). mothers’ perceptions of the helpfulness of formal and informal supports.